Change of Government and the Impact towards Royal Malaysian Police - A/L Selvarajoo, Prasad Money Raj; Asli, Muhammad Asri Mohd (JPAS (Journal of Public Administration Studies), 2024)
Political stability plays a pivotal role to determine country’s progress and development. Between the year of 2020 to 2022, Malaysia experienced political crisis that have never before happened in the country. It begins with what was known as the Sheraton Move leading to the collapse of two successive coalition governments and the resignation of two prime ministers in less than 18 months. This change of government caused by party switching or coalition among members of parliament raise concerns about public administration practices. What are the factors that influence public servant’s motivation to perform better is largely unanswered. What are the impacts of change of government towards job motivation and job satisfaction of the public servant such as police officer? This question is rather significant since the construct of change of government involve the process of revising existing public policies and strategies. This paper provides discussion about the impacts of change of government towards job motivation and job satisfaction based on the analysis of five experts and opinions of 48 police officers.